Immunomodulatory, cytotoxic and antileishmanial activity of Setaria megaphylla - Jude E. Okokon; Ashana Dar; M. Iqbal Choudhary (International Journal of Phytomedicine, 2012)
Cytotoxic, antioxidative burst and antileishmanial properties of leaf extract and fractions of Setaria megaphylla were investigated to ascertain the folkloric claims of its potency in inflammatory diseases and infections. The leaf extract and fractions of Setaria megaphylla were investigated for anticancer activity against HeLa cells using SRB method and DNA interaction activity using gel electrophoresis. Antioxidative burst activity of the extract in whole blood, neutrophils and macrophages was also investigated using luminol/lucigenin-based chemiluminescence assay. The extract and fractions were similarly screened for antileishmanial activity against promastigotes of Leishmania major in vitro. The GCMS analysis of the most active fraction against HeLa cells was carried out. The leaf extract was found to exert significant anticancer activity with the hexane fraction exhibiting the most pronounced effect. The crude extract and the fractions did not interact with DNA when investigated using electrophoresis. The extract prominently inhibited oxidative burst activity in whole blood, isolated polymorphonuclear cells (PMNs) and mononuclear cells (MNCs) when two different phagocytosis activators (serum opsonizing zymosan-A and PMA) were used. The extract also exhibited moderate antileishmanial activity against promastigotes of Leishmania major in vitro. GCMS analysis of active fraction revealed pharmacologically active compounds. These results suggest that the leaf extract/fractions of S. megaphylla possesses cytotoxic, antioxidative burst and antileishmanial activities and these justify its use in ethnomedicine to treat inflammatory diseases and microbial infections and can be exploited in primary healthcare.